Lingvo-philosophic interpretation of the notions ‘sense of the text’, ‘structure of the text’ (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the main ways of teaching language and to translate some material in linguisticand non-linguistic high schools; the author describes two main logico-semantic relation (enumerative)between segments of the text important for the translation process. Traditional and non-traditional waysof representing this relation is analyzed to picture the ways to keep the idea of the text author.On the basis of lingo-philosophic interpretation the author differentiates meaningful elements ofinner-translation, distinguishes main sensible and structural elements of the combination ‘sense of thetext’, ‘structure of the text’, that help to perceive and get resultative approach in teaching language andteaching to translate.